KORELASI ANTARA KEMAMPUAN MEMBACA PEMAHAMAN DENGAN HASIL BELAJAR DALAM PEMBELAJARAN TEMATIK PADA SISWA KELAS V SD NO. 2 KEKERAN (Adi Widya: Jurnal Pendidikan Dasar, 2022)
This study aims to determine 1) reading comprehension skills, 2) learning outcomes in thematic learning, 3) the relationship between reading comprehension skills and learning outcomes in thematic learning in class V SD No. 2 Kekeran. This type of research is a correlation study with the research sample of the fifth grade students of SD No. 2 Kekeran totaling 30 students with saturated sample technique. The instrument for collecting data was in the form of a reading comprehension test and thematic learning outcomes in the cognitive domain on theme 2: Clean Air for Health. The results of the analysis showed that 36.67% of students obtained the ability to read comprehension in very good categories, 40% of students obtained learning outcomes in thematic learning in very good categories, and there was a relationship between reading comprehension skills and learning outcomes in thematic learning of 0.723 with a strong category. by getting r_count of 0.723> r table 0.374. and the significance is 0.000 <0.05